2018
DOI: 10.3762/bjnano.9.119
|View full text |Cite
|
Sign up to set email alerts
|

Artifacts in time-resolved Kelvin probe force microscopy

Abstract: Kelvin probe force microscopy (KPFM) has been used for the characterization of metals, insulators, and semiconducting materials on the nanometer scale. Especially in semiconductors, the charge dynamics are of high interest. Recently, several techniques for time-resolved measurements with time resolution down to picoseconds have been developed, many times using a modulated excitation signal, e.g., light modulation or bias modulation that induces changes in the charge carrier distribution. For fast modulation fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…For the modulated light a fast switched diode laser (PicoQuant FSL500) was externally triggered using user-defined signal patterns, avoiding any frequencies which could lead to artifacts due to frequency mixing. [49] Device Processing: Devices were fabricated by two subsequent direct photolithography steps. First, the contacts were defined by removing i-ZnO using a solution of aqueous HCl (0.5%) for 15 s. Subsequently, without removing the photoresist, the Cr/Au contacts (thickness of 6 and 30 nm, respectively) were deposited by sputtering immediately after opening the via to prevent oxidation.…”
Section: Methodsmentioning
confidence: 99%
“…For the modulated light a fast switched diode laser (PicoQuant FSL500) was externally triggered using user-defined signal patterns, avoiding any frequencies which could lead to artifacts due to frequency mixing. [49] Device Processing: Devices were fabricated by two subsequent direct photolithography steps. First, the contacts were defined by removing i-ZnO using a solution of aqueous HCl (0.5%) for 15 s. Subsequently, without removing the photoresist, the Cr/Au contacts (thickness of 6 and 30 nm, respectively) were deposited by sputtering immediately after opening the via to prevent oxidation.…”
Section: Methodsmentioning
confidence: 99%
“…The surface photovoltage is defined as: SPV = CPD under illumination − CPD in dark . For the modulated light, a fast switched diode laser (PicoQuant FSL500) was externally triggered via user-defined signal patterns, avoiding any frequencies which could lead to artifacts due to frequency mixing 68 . The light sources have an optical power of ∼4.5 mW (with an intensity of~100 mW cm −2 ) and an illumination angle of 28°, to ensure illumination of the sample under the tip and cantilever beam.…”
Section: Jð1þ Jð0þmentioning
confidence: 99%
“… 24 , 27 , 28 Limitations and possible artifacts of this approach have also been investigated by a number of groups. 27 , 29 Murawski et al reported on a dual-closed loop system that removes crosstalk artifacts in the topography channel originating from an incorrect voltage applied by the KPFM feedback loop. 28 We overcome this artifact by detecting the first-harmonic signal F ω directly in open-loop measurements; however, we note that in this case additionally the F 2ω signal has to be considered to separate transient V cpd changes from capacitive changes.…”
Section: Introductionmentioning
confidence: 99%